Removal of emerging contaminants from wastewater using advanced treatments. A review - Morin-Crini, Nadia; Lichtfouse, Eric; Fourmentin, Marc; Ribeiro, Ana Rita Lado; Noutsopoulos, Constantinos; Mapelli, Francesca; Fenyvesi, Éva; Vieira, Melissa Gurgel Adeodato; Picos-Corrales, Lorenzo A.; Moreno-Piraján, Juan Carlos; Giraldo, Liliana; Sohajda, Tamás; et al. (Environmental chemistry letters, 2022)
The rise of emerging contaminants in waters challenges the scientific community and water treatment stakeholders to design remediation techniques that are simple, practical, inexpensive, effective, and environmentally friendly. Emerging contaminants include antibiotics, hormones, illicit drugs, endocrine disruptors, cosmetics, personal care products, pesticides, surfactants, industrial products, microplastics, nanoparticles, and nanomaterials. Removing those contaminants is not easy because classical wastewater treatment systems are not designed to handle emerging contaminants, and contaminants often occur as traces in complex organo-mineral mixtures. Here, we review advanced treatments for the removal of emerging contaminants in wastewater, with focus on adsorption-oriented processes using non-conventional adsorbents such as cyclodextrin polymers, metal–organic frameworks, molecularly imprinted polymers, chitosan, and nanocellulose. We describe biological-based technologies for the degradation and removal of emerging contaminants. Then, we present advanced oxidation processes as the most promising strategies because of their simplicity and efficiency.